Model Implementasi Pembelajaran Kitab Alala Di Pondok Pesantren Langitan Widang Tuban - Murtaufiq, Sudarto (MADINAH, 2018)
The writer is interested in raising the title "The Implementation Model of Kitab Alala Learning in Al Falahiyah Islamic Elementary School Pesantren Langitan Widan Tuban: An implementation model" for being motivated by a fact that the number of new students in MI al-Falahiyah behave less patiently in dealing with exams and in learning the Qur'an. Pesantren Langitan Widang Tuban is one of the old Islamic boarding schools organizing its education system informally. This Islamic boarding school instills education littered fully with both religious values ​​and the nation's noble ones. The purpose of this study is to find out the implementation model of the learning of Kitab Alala in MI al-Falahiyah Pesantren Widang Tuban. This study uses a descriptive qualitative approach. Data collection is carried out through such methods as observations, interviews and documents. The results of the study show that the implementation model of the learning of Kitab Alala in al-Falahiyah Islamic Elementary School Pesantren Langitan Widang Tuban is through four models, namely the so-called mauidhoh, habituation, the qudwah (exemplary), targhib and tarhib.